Distinct Functions of Acyl/Alkyl Dihydroxyacetonephosphate Reductase in Peroxisomes and Endoplasmic Reticulum - Honsho, Masanori; Tanaka, Megumi; Zoeller, Raphael A.; Fujiki, Yukio (Frontiers in Cell and Developmental Biology, 2020)
Plasmalogens belong to the class of ether glycerophospholipids characterized by a vinyl-ether bond at the sn-1 position of the glycerol backbone. Plasmalogen biosynthesis is initiated in peroxisomes. At the third step of plasmalogen synthesis, alkyl-dihydroxyacetonephosphate (DHAP) is enzymatically reduced to 1-alkyl-sn-glycero-3-phospate by acyl/alkyl DHAP reductase (ADHAPR), whose activity is found in both peroxisomes and microsomes. We herein show that knockdown of ADHAPR in HeLa cells reduced the synthesis of ethanolamine plasmalogen (PlsEtn), similar to the Chinese hamster ovary cell mutant FAA.K1B deficient in ADHAPR activity. Endogenous ADHAPR and ectopically expressed FLAG-tagged ADHAPR were localized to peroxisomes and endoplasmic reticulum (ER) as a type I integral membrane protein in HeLa cells. ADHAPR targets to peroxisomes via a Pex19p-dependent class I pathway, while ADHAPR is inserted into the ER via the SRP-dependent mechanism. The ADHAPR mutant lacking the N-terminal domain preferentially targets to the ER, restoring the reduced level of PlsEtn synthesis in FAA.K1B cell. In contrast, the expression of full-length ADHAPR in the mutant cells elevates the synthesis of phosphatidylethanolamine, but not PlsEtn. Taken together, these results suggest that the third step of plasmalogen synthesis is mediated by ER-localized ADHAPR.